Peran Perserikatan Bangsa-Bangsa dalam Penyelesaian Pelanggaran HAM Terhadap Etnis Rohingya di Myanmar: Perspektif Responsibility to Protect Concept - Fadilah, Fatma Putri; Hakim, Moh. Akmal Taris; Frefy, Fyo Akbar Putra; Wahyuni, Ridha (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Responsibility to Protect (R2P) is an international principle that emphasizes the obligation of every country to protect the human rights of its citizens. Although human rights violations against the Rohingya ethnic group in Myanmar are an internal problem, resolving them is still difficult. Further evaluation by the UN is needed to ensure the effectiveness of R2P implementation. The UN implements R2P through the Security Council and Human Rights Council to overcome the humanitarian crisis against the Rohingya ethnic group. The type of research used is literature study by reviewing existing literature related to the written topic. The method used is a qualitative research method with the data source used in the form of secondary data obtained from several national journals, articles and previous research. The result is that we can see that the implementation of R2P in this conflict is still facing difficulties, as shown by the UN Presidential Statement in November 2017. The role of the UN Human Rights Council helps in resolving cases of human rights violations against the Rohingya ethnic group, although the implementation of R2P is difficult in Myanmar's internal conflict with the Rohingya ethnic group.